2014
DOI: 10.1007/s11701-014-0482-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and implementation results of an interactive computerized surgical checklist for robotic-assisted gynecologic surgery

Abstract: To address surgical complications, the World Health Organization (WHO) developed the Safe Surgery Saves Lives Checklist. With the foundation of the WHO's checklist, a robotic-specific checklist (RORCC) was developed using standardized content and face validity methods. The RORCC was implemented in a high volume gynecological (GYN) specialty group using minimally invasive robotic-assisted surgery. Data were abstracted from patients undergoing GYN procedures from four GYN surgeons at an urban, community hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…The original Dutch and the Indian SURPASS studies did not report on unplanned readmissions, so ours is the first to investigate effects of SURPASS checklists use on this. While several WHO SSC studies have shown a reduction in readmissions 87,91,98,108 , other such studies showed no such change 88,105 .…”
Section: Effects On Patient Outcome Of Adding the Surpass Checklists mentioning
confidence: 94%
See 1 more Smart Citation
“…The original Dutch and the Indian SURPASS studies did not report on unplanned readmissions, so ours is the first to investigate effects of SURPASS checklists use on this. While several WHO SSC studies have shown a reduction in readmissions 87,91,98,108 , other such studies showed no such change 88,105 .…”
Section: Effects On Patient Outcome Of Adding the Surpass Checklists mentioning
confidence: 94%
“…Favourable patient outcomes were associated with the use of WHO SSC in several studies with reductions in complications 10,19,92,[94][95][96][97][98][99][100][101][102][103][104] , mortality 10,11,62,88,94,102,105,106 , unplanned reoperations 10,19,99,107 , and unplanned readmissions 91,98,108 , LOS 19,89,105,106 , while other studies reported no significant changes after introduction of the WHO SSC as to complications 89,93,106,[109][110][111][112][113][114] , mortality 19,89,91,93,95,[97][98][99]…”
Section: Re-admission Los Othersmentioning
confidence: 99%
“…The study characteristics are presented in Table S2. Six of the 12 studies reviewed focused on laparoscopic procedures (Al‐Hakim, ; Hafford et al., ; Murji et al., ; Sevdalis, Hull, & Birnbach, ; Silvennoinen, Antikainen, & Mecklin, ; Stavroulis, Cutner, & Liao, ) and 6 focused on robotic‐assisted surgeries (Allers et al., ; Catchpole et al., ; Friedman, Lendvay, & Hannaford, ; Jing & Honey, ; McCarroll et al., ; Randell et al., ). Six studies used a qualitative methodology, all of which used thematic data analysis with the exception of Silvennoinen et al.…”
Section: Resultsmentioning
confidence: 99%
“…5–7 However, evidence supporting the use of perioperative bundles for hysterectomy and what processes they might contain is lacking despite the fact that over 400,000 women per year undergo the procedure in the U.S. 8 Therefore, the aim of our study was to evaluate a perioperative bundle of evidence-based processes for benign hysterectomy and retrospectively evaluate its impact on postoperative outcomes using a statewide hysterectomy database.…”
Section: Introductionmentioning
confidence: 99%